2006
DOI: 10.2341/04-171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bur Grinding on the Bond Strength of Self–etching Adhesives

Abstract: SUMMARYThis study compared the microtensile bond strength (MTBS) of three all-in-one adhesive systems and a two-step system using two types of burs to prepare the dentin surfaces. Flat coronal surfaces of 24 extracted human molars were produced using either regular-grit or superfine-grit diamond burs. Resin composite was then bonded to equal numbers of these surfaces using one of the four adhesives: Clearfil SE Bond (CSE), GBond (GB), SSB-200 (SSB) or Prompt L-Pop (PLP). After storage for 24 hours in 37°C dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
29
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 14 publications
6
29
0
6
Order By: Relevance
“…In contrast, the two-step adhesive SE showed significantly higher values compared with those of the single-step adhesives. These results agreed with other studies which reported that there were no significant differences in MTBS between ABS and S3 31) , whereas higher values were observed for SE compared with AD and ABS 32) .…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, the two-step adhesive SE showed significantly higher values compared with those of the single-step adhesives. These results agreed with other studies which reported that there were no significant differences in MTBS between ABS and S3 31) , whereas higher values were observed for SE compared with AD and ABS 32) .…”
Section: Discussionsupporting
confidence: 82%
“…These SEM analyses suggest that the experimental one-step adhesives that had produced MDP-Ca salt more than 37.2 mg/g led to an increase in the probability that the demineralized dentin zone will be developed at the peritubular dentin. This was because both calcium and phosphorous element signals assigned to the byproducts produced by demineralization were concentrated at the peeled resin tag portions more intensely than the fractured adhesive surface from the intertubular dentin surface, since the peritubular dentin was demineralized by these adhesives more strongly than the intertubular dentin 25) . In contrast, any significant difference in the enamel bond strength was not observed before and after thermocyclying, even though the amount of MDP-Ca salt reached 78.3 mg/g.…”
Section: Discussionmentioning
confidence: 95%
“…This was possibly because the fractured peritubular dentinal collagen fibers that had not impregnated with one-step adhesive were clearly seen at the circumference inside the dentinal tubules 25) and at the bases of the resin tags peeled off from the dentinal tubules. These SEM analyses suggest that the experimental one-step adhesives that had produced MDP-Ca salt more than 37.2 mg/g led to an increase in the probability that the demineralized dentin zone will be developed at the peritubular dentin.…”
Section: Discussionmentioning
confidence: 99%
“…이러한 접착시스템은 산부식, 프라이밍 및 접착과 같은 다단계의 접착과정을 단순화시키기 위해 2단계 와 단일단계의 접착시스템으로 개발되어 사용되고 있다 [2][3][4] . 2단계 접착시스템 중 자가부식 프라이머 접착시스템 (selfetching primer adhesive system)은 자가부식 프라이머 용액과 접착레진 용액으로 공급되고 있으며, 법랑질과 상아 질 모두에 우수한 접착력을 보이고 있다 5) .…”
unclassified
“…또한 프라이머 에 포함된 인산 에스테르 (phosphoric ester)와 같은 산성 단량체에 의해 부식과 프라이밍 기능이 동시에 이루어지기 때문에 산부식 접착시스템에서 흔히 발생할 수 있는 산부식 후 과도한 건조나 습윤에 의한 노출된 상아질 콜라겐의 불 충분한 레진침투와 같은 문제점을 막을 수 있다 6,7) . 접착시스템의 치질에 대한 접착은 삭제기구에 의해 치질 표면에 형성된 도말층 (smear layer)의 두께와 프라이머 및 접착제의 적용방식 등에 의해 영향을 받을 수 있다 2,[8][9][10] . 자가부식 프라이머 접착시스템은 프라이머의 조성과 산성 단량체에 의해 다양한 산도를 갖기 때문에 다양한 부식성을 나타낸다 4,11,12) .…”
unclassified